Home Bias in Open Economy Financial Macroeconomics - Coeurdacier, Nicolas; Rey, Hélène (Journal of Economic Literature, 2013)
Home bias is a perennial feature of international capital markets. We review various explanations of this puzzling phenomenon highlighting recent developments in macroeconomic modeling that incorporate international portfolio choices in standard two-country general equilibrium models. We refer to this new literature as Open Economy Financial Macroeconomics. We focus on three broad classes of explanations: (i) hedging motives in frictionless financial markets (real exchange rate and nontradable income risk), (ii) asset trade costs in international financial markets (such as transaction costs or differences in tax treatments between national and foreign assets), and (iii) informational frictions and behavioral biases. Recent theories call for new portfolio facts beyond equity home bias. We present new evidence on cross-border asset holdings across different types of assets: equities, bonds and bank lending and new micro data on institutional holdings of equity at the fund level. These data should inform macroeconomic modeling of the open economy and a growing literature of models of delegated investment. (JEL E13, F41, G11, G12, G15)